The effects of 6 months specific aerobic gymnastic training on motor abilities in 10 - 12 years old boys - Mehrtash, M.; Rohani, H.; Farzaneh, E.; Nasiri, R. (Science of Gymnastics Journal, 2015)
The purpose of this study was to investigate the effect of six months specific aerobic gymnastic training on motor abilities in 10-12 years old boys. Eighteen boys (aged 10-12 years old) volunteered to participate in the 6 months aerobic gymnastic training. Some motor ability parameters were measured weekly in addition to pre training. Data were analyzed using one-way ANOVA with repeated measures. The mean values of Chin-Up in 30 Seconds, Legs Lift in 30 sec, Horizontal Jump and Press Handstand test records were significantly changed after 6 months training (p<0.05).The Rope Climbing Using Legs/Feet records were significantly decreased (promoted) after 6 months specific training in aerobic gymnasts. Similarly, Tuck up Trunk and Leg Flexion records were significantly increased in the first, 3rd and last month evaluations (p<0.05).The records of Single Leg Squats test were significantly increased in both legs approximately similar to a higher value in pre training for right leg (p<0.05). Based on the results of this study it can be concluded that specific training in aerobic gymnastic, (independent of growth and maturation) causes positive changes in motor abilities in 10-12 years old boys.